Cytological and molecular characterization of some wheat (Triticum aestivum l.) cultivars - Abd El-Gawwad, Mona H. (2009)
wheat (Triticum aestivum L.) belongs to Poaceae family. Ninetyfive percent of wheats grown today are of the hexaploid type comprising three genomes A, B and D. Each of these genomes has seven chromosome pairs. The remaining 5% is durum (Triticum turgidum L., var. durum) tetraploid wheat (Heun et al., 1997). The genomic formula of 2n=6x=42, AABBDD is believed to have been arisen as a result of allohexaploid between an AABB tetraploid, Triticum turgidum and with DD diploid genome, Aegilops squarrosa (Triticum tauschii) and the AA genome of hexaploid wheats has its origin from Triticum urartu, (Miller, 1987; Jahan and Vahidy, 1989). The wheat genome is 17000 Mb (Hartl and Jones, 2001).
Includes references.
1
Keywords: Wheat -- Cytology; Wheat -- Varieties